Модернизация традиционного общества: проблемы и перспективы - Квашенко, В. Р.; Селезько, Р. О. (ХНУРЕ, 2020)
The article discusses the problems of modernization of traditional society in the development of the modern world. It is argued that the modernization of society in the classical sense is fundamentally associated with a change in the methods of exercising political power. In the context of globalization and modernization, the behavior of the ruling class of a traditional society is changing, but the consequences of such a change are not always predictable.
Keywords: философия; модернизация традиционного общества